ANALISIS PEMAHAMAN METODOLOGI PENELITIAN PADA PESERTA PRAKTIKUM PENELITIAN - Romlah, Romlah; Karimah, Ummah; Shofiyah, Siti; Asni, Asni; Syifa Annaqi, Danish; Hulwani, Zati (Asosiasi Dosen PTKIS Indonesia, 2023)
A scientific knowledge or science can be obtained through steps in a systematic way in its preparation and implementation and refers to the forms of research so as to find data for certain purposes and uses. The purpose of the study was to determine the understanding of research methodology courses in students participating in research practicum. This type of research is descriptive research. The population in this study were all participants in the research practicum of the Islamic religious education study program at Universitas Muhammadiyah Jakarta, consisting of 122 students. The sampling technique was purposive sampling. The data collection instrument used was a multiple choice type closed questionnaire instrument. Data analysis was calculated using the percentage formula of the level of understanding. The results of data analysis showed that 76.1% experienced a moderate level of understanding. The conclusion for the level of understanding of students participating in the research practicum has a level of understanding of research methodology is identifying, selecting, formulating problems, problem sources, selecting problems, formulating problems, and preparing a framework.